Management of Facilities and Infrastructure at SMK Negeri 1 Sinjai, Sinjai Regency - Saleh, Sirajuddin; Angraeni, Enni; Nasrullah, Muh. (Universitas Negeri Makassar, 2022)
Facilities and infrastructure have a very important role in the learning process, in order to create a comfortable and conducive learning process. This research is a qualitative descriptive study that aims to determine the Management of Facilities and Infrastructure at SMK Negeri 1 Sinjai, Sinjai Regency. The number of informants in this study were 5 people, namely, the principal of SMK Negeri 1 Sinjai, 3 managers of facilities and infrastructure, 1 teacher of SMK Negeri 1 Sinjai. The results of the study indicate that the management of facilities and infrastructure at SMK Negeri 1 Sinjai, Sinjai Regency arises because there are still some facilities and infrastructure management that have not been managed properly, namely the use of facilities and infrastructure. The use of infrastructure, for example, a room that can still be used is not maintained so that it becomes damaged